Measuring and explaining political tolerance among adolescents: insights from the International Civic and Citizenship Education Study 2016 - Johanna F. Ziemes (Large-scale Assessments in Education)
Abstract Background Tolerance is a prerequisite for deliberative democracies. Therefore, fostering tolerance is an important task for educational systems in democracies. In the present study, the concepts of social and political tolerance were disentangled and applied to the measurement approaches of the International Civic and Citizenship Education Study 2016 (ICCS 2016). A single scale of political tolerance was proposed by identifying items on equal rights of women and men, different racial and ethnic groups and immigrants that capture the support of equal political rights. Previous research indicates different approaches that might be used to foster tolerance in schools. Methods This study used the rarely applied alignment method to identify a political tolerance scale that was sufficiently invariant in the 15 participating European educational systems. The alignment method identifies solutions with minimal amounts of non-invariance. Multilevel regression analyses are used to identify which aspects of schooling are predictive of political tolerance at the student and at the school level. Results The alignment analyses revealed a sufficiently invariant solution for the 15 education systems that could be used in regression analyses. While cognitive learning showed only a weak relationship with political tolerance, teacher fairness was relevant at student and school level. An open classroom climate was a positive predictor with relevant strength only at school level. Further multigroup analyses indicated that the results at the student level were stable between countries, while school level indicators varied more strongly between countries. Conclusions Researchers need to acknowledge the conceptual differences between social and political tolerance in their measurement approaches. The alignment method can be useful to create scales that are comparable between many different educational systems. While educational systems differ strongly in their school level variance of political tolerance, teachers can play an important role in fostering political tolerance at the student level.